Biochemical Effects of Energy Drinks Alone or in Combination with Alcohol in Normal Albino Rats - Ugwuja, Emmanuel (Tabriz University of Medical Sciences, 2014)
Purpose: To determine the biochemical effects of energy drink alone or in combination with alcohol in normal albino rats. Methods: Twenty male albino rats weighing 160-180g were assigned into groups A-E of four rats per group. Group A and B rats were given low and high doses of ED, respectively, groups C and D were administered low and high doses of EDmA, respectively while group E rats were given distilled water and served as control. The treatment lasted for 30 days after which the animals were killed and their blood collected for laboratory analyses using standard methods. Results: There were no significant differences in body weight, packed cell volume and haemoglobin concentration with either administration of ED or EDmA in comparison to the control. Energy drink alone or EDmA has significant effects on total white blood cell count, plasma potassium, calcium, renal functions, liver enzymes and plasma triglycerides, with EDmA having more effects than ED alone, except for body weight where the energy drink alone has higher effect. Conclusion: Consumption of energy drink alone or in combination with alcohol is associated with significant alterations in some biochemical parameters. Caution should be exercised while consuming either of them. Public health education is urgently needed to correct the wrong impression already formed by the unsuspecting consumers, especially the youths.